2014
DOI: 10.1177/1071100714552480
|View full text |Cite
|
Sign up to set email alerts
|

Natural History of Nonoperatively Treated Osteochondral Lesions of the Talus

Abstract: BACKGROUND We hypothesized that patients undergoing nonoperative treatment for asymptomatic or minimally symptomatic osteochondral lesions of the talus (OLTs) would not deteriorate clinically or radiologically over time. METHODS Forty-eight patients (mean age = 48 years; range, 13-78 years) with an OLT confirmed by magnetic resonance imaging (MRI) who had not undergone ankle joint surgery were retrospectively reviewed. All patients were evaluated after a minimum follow-up of 2 years (mean = 52 months; range, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 26 publications
2
54
0
1
Order By: Relevance
“…This mechanism of injury is supported by the anatomic distribution of talar osteochondral lesions (OCLs), with the medial talus affected nearly twice as frequently as the lateral talus, and the mid‐one third of the talar dome affected four times more commonly than the anterior and posterior thirds combined . Evidence suggest that the majority (as high as 95%) of severe ankle sprains result in OCLs and over half of patients with OCLs develop OA . Ligament injury resulting in chronic ankle instability is a common sequelae to severe sprain, and approximately 15% of ankle sprains are recurrences .…”
Section: Etiology Of Talocrural Oa—the Association Between Cartilage mentioning
confidence: 99%
“…This mechanism of injury is supported by the anatomic distribution of talar osteochondral lesions (OCLs), with the medial talus affected nearly twice as frequently as the lateral talus, and the mid‐one third of the talar dome affected four times more commonly than the anterior and posterior thirds combined . Evidence suggest that the majority (as high as 95%) of severe ankle sprains result in OCLs and over half of patients with OCLs develop OA . Ligament injury resulting in chronic ankle instability is a common sequelae to severe sprain, and approximately 15% of ankle sprains are recurrences .…”
Section: Etiology Of Talocrural Oa—the Association Between Cartilage mentioning
confidence: 99%
“…Only 6 lesions were associated with moderate (VAS 4-6) and one with severe (VAS 7-9) pain. Beyond that, Klammer et al detected no correlation between clinical parameters and the pain intensity according to the VAS [24].…”
Section: Discussionmentioning
confidence: 95%
“…In a retrospective study Klammer et al [24] examined 48 patients with 50 osteochondral lesions of the talus that received a conservative treatment. The visual analog scale (VAS) was used for the evaluation of the pain intensity at the time of follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of a talar cyst remains controversial, although some have supported the valve mechanism of the damaged cartilage (12). Klammer et al (13) reported conservative treatment and close observation were recommended to treat mild symptoms of a small cyst owing to its slow progression. When the talus is extensively destroyed, the absence of timely surgery will increase the risk of pathologic fracture and damage to the articular cartilage, leading to persistent swelling and pain of the subtalar joint and ankle joint.…”
Section: Discussionmentioning
confidence: 99%